Pemahaman, amalan dan permasalahan guru Pendidikan Islam dalam pelaksanaan Pentaksiran Berasaskan Sekolah (PBS) dalam Kurikulum Baru Sekolah Menengah (KBSM) - Adam, Norhaslina (2013)
This study aims to explore the understanding of Islamic studies teachers (GPI) in the implementation of the School-Based Assessment (SBA) in the New Curriculum for Secondary Schools (KBSM) in terms of the level of understanding, level of practices and problems faced by the Islamic teachers when implementing PBS in their respective school own. In addition, this study also examined the differences GPI level of understanding based on gender and see if there is a correlation between the level of understanding, level of practices and problems among them. A total of 70 people GPI consists of 16 schools in the district of Pontian, Johor were randomly selected for the study. Questionnaire, which has 0.8027 Cronbach Alpha value used to measure the level of understanding, level of practices and the level of problems in the implementation of PBS GPI in the KBSM, and the next level of understanding of the differences and relationships GPI determined. GPI understanding measured using descriptive statistical analysis, frequency, percentage, mean and standard deviation. To get an understanding of the relationship with the level of problems, the Pearson correlation test was used. The findings showed that the level of understanding, level of practices and problems faced by the GPI is at a medium level of overall (mean = 3:62). The study showed that there is a clear relationship between the level of understanding of the level of implementation of PBS with value (r=0.342,p =0.004<0.01) and moderation relationship but strong value that (r=-0.443,p =0.000<0.01) between the level of understanding of the level of GPI problems in school There was no significant difference in the level of understanding on the implementation of gender based GPI PBS with value (t = 0.695,ρ <0.490).There are some suggestions for further research are described to further strengthen implementation of the School-Based Assessment for the realization of the Ministry of Education to create a well-balanced human development in terms of the Physical, Emotional, Spiritual and Intellectual not dependent on the level of their examination alone.